Modeling recreation demand with respondent-reported driving cost and stated cost of travel time - Ovaskainen, Ville; Neuvonen, Marjo; Pouta, Eija (it, 2011)
Respondent-reported driving and time costs are used to represent the individual trip price for a solution to a calibration problem in the travel cost method (Randall 1994). After considering recreationists perceptions of driving costs and travel time, models based on individual driving costs and stated costs of travel time are compared to standard-type specifications with wagebased time costs. Respondent-reported driving costs appear to be a working tool for calibrating the welfare measures. The willingness to pay to reduce travel time was logically related to respondent and trip characteristics and had reasonable effects on benefit estimates.
Keywords: Ma; matkailu; travel costs; tourism; kustannukset; matkakustannukset